The Feasibility of Isra'īliyyāt History in Interpretation Al-Qur'an - Abdul Matin Bin Salman (al-Afkar, Journal For Islamic Studies, 2023)
This study aims to evaluate the role of isrā'īliyyāt as a source of interpretation of the Qur'an by integrating the rules of the validity of hadith within the framework of the context of interpreting the Qur'an. This research deepens the analysis of the existence of isrā'īliyyāt in the method of exegesis of the Qur'an bi al-m'athūr and its impact on the credibility of that interpretation. This research uses a critical analysis approach to understand and validate the use of isrā'īliyyāt in the interpretation of the Al-Qur'an. This research analyzes various tafsir works to understand the ulama's approach to the history of isrā'īliyyāt and assess the credibility of the interpretation by considering the criteria for the authenticity of the hadith. Data is collected through analysis of selected interpretive works. This research concludes by evaluating the implications of the findings for Muslims' understanding of the Koran. The findings of this research reveal two main aspects: (1) variability in approaches to validating the validity of isrā'īliyyāt history by tafsir scholars. Despite detailed investigations into these narrations, their interpretations are often inconsistent with the characteristics of the Qur'an, resulting in doubt in the results of the interpretation. (2) The lack of emphasis on the standard rules of authentic history relating to isrā'īliyyāt by tafsir scholars, which has an impact on the vulnerability of their works to criticism and controversy. This research encourages the need for a stronger critical approach to isrā'īliyyāt in the interpretation of the Qur'an. Integrating historical validity standards to produce more accurate and credible interpretations is the recommended solution. The significance of this research is undeniable, because its implications can influence our in-depth understanding of the Qur'an and maintain the integrity of interpretation. Through a more careful approach to isrā’īliyyāt, we can strengthen the foundation of our knowledge of the message of the Qur'an, avoid ambiguous interpretations, and advance our understanding of the religion.